Burden of stigma among tuberculosis patients: a cross-sectional study - Kallepalli, Swarna S. K.; Garapati, Sridevi; Bhimarasetty, Devimadhavi; Pethala , Sujatha (International Journal Of Community Medicine And Public Health, 2023)
Background: Tuberculosis (TB) is a significant public health problem in populous countries like India. Despite having effective treatment, social stigma still exists and it manifest as social exclusion (enacted stigma) or perception of it (felt stigma). The main causes of stigma are fear of TB and the terrible effects the disease will have on affected people and their family’s health, finances, personal lives, and social standing. Delay in diagnosis and treatment are brought on by stigma, resulting in adverse treatment outcomes and thus prevent TB from being eliminated. The objectives of the study were to (a) estimate the burden of stigma experienced by tuberculosis patients; and (b) identify the factors associated with stigma. Methods: A cross-sectional analytical observational study was carried out among 100 TB patients above 18 years of age in the months of September - November 2022. Multistage random sampling was used to select the study participants from different peripheral health institutes. Data was collected using predesigned, pretested proforma from explanatory model interview catalogue developed by WHO. Data was collected after obtaining informed consent and analysed by using SPSS 21. Results: Majority of patients (59%) perceived stigma. Many (73%) revealed that they desire to keep others from knowing about their condition, felt that others would think less of patient’s family (66%) and avoided them (69%) due to disease. Conclusions: Patients with TB still experience greater stigma at home, among friends, and at work. Sensitization of family and awareness among the public is essential to combat stigma.